RANCANG BANGUN ALAT PEMBERI PAKAN BERBASIS IOT PADA TERNAK AYAM PETELUR - Ningsih, Dwi Wahyu; Sulaiman, Husni; Perawati, Perawati (journal Informatika, Multimedia, dan Informasi, 2024)
The aim of this study: (1) Desing and build automatic feeding equipment for laying hens. (2) Monitoring feeding equipment for laying hens.This research uses the waterfall research method, that is, step by step you have to wait for the completion of the previous stage and proceed sequentially, the stage will not be carried out before the stages are completed. Waterfall research has several stages that is: (1) Condition, (2) Design stages, (3) Application, (4) Verification, (5) Maintenance. The results of this research show that: (1) The design of IoT-based feeding equipment for laying hens is designed using HC-SR04 ultrasonic sensor, NodeMCU, PCB, Servo Motor, Rtc, L298N Motor Drive, 12v Stepper Motor, Android Smartphone and Blynk Application and 12v Adapter. (2) The design of an IoT-based feeding device for laying hens has been carried out in a chicken coop belonging to one of the residents in Palimassang, Padang Village. The benefit of designing IoT-based feeding equipment for laying hens is that the owner can carry out other activities so that when the IoT-based feeding schedule for laying hens arrives, it can be done automatically with the schedule that has been input into the blynk application at the same time as the current time so that the container moves. Blynk application for monitoring feed contents in containers obtained from ultrasonic sensors. The Blynk application will display the feed level in the container at any time and will notify you on your smartphone when the feed content is insufficient in the container in the cage.